2012
DOI: 10.1002/pon.3133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perceived social support on the mental health and health‐related quality of life in cancer patients: results from a nationwide, multicenter survey in South Korea

Abstract: Objective We investigated whether and how perceived social support is associated with depression and quality of life among patients with various cancer diagnoses. Methods Data were collected from 1930 cancer patients treated at the National Cancer Center and nine regional cancer centers across Korea. The Duke‐UNC functional social support scale was used to measure the perceived social support, and the PHQ‐9 and the EORTC QLQ‐C30 were used to measure the cancer patients' depression levels and quality of life, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
110
2
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 40 publications
10
110
2
4
Order By: Relevance
“…In study carried by Eom et al [13], perceived social support was found to be associated with mental health and QOL; specifically, low perceived social support was associated with low QOL in this study. This result was consistent with previous studies that showed that higher perceived social support was associated with a higher QOL [16;17].…”
Section: Int Conf Society Health Welfare 2014mentioning
confidence: 62%
See 1 more Smart Citation
“…In study carried by Eom et al [13], perceived social support was found to be associated with mental health and QOL; specifically, low perceived social support was associated with low QOL in this study. This result was consistent with previous studies that showed that higher perceived social support was associated with a higher QOL [16;17].…”
Section: Int Conf Society Health Welfare 2014mentioning
confidence: 62%
“…that patients recover after treatment, supportive attitudes may weaken after primary treatment [13]. Those with more years since diagnosis trended toward lower perceived social support in this study.…”
Section: Int Conf Society Health Welfare 2014mentioning
confidence: 71%
“…Subjects (n = 1930) with low perceived social support reported significantly higher levels of depression, lower scores on all functional scales, and lower global health quality of life scale scores in a nationwide study. Researchers concluded that cancer patients' perceived social support was directly associated with mental health and the quality of life in cancer patients, rather than having a "stress-buffering" effect (16).…”
Section: Discussionmentioning
confidence: 99%
“…El apoyo social, de acuerdo con la literatura previa (26,27) , se asocia con los niveles de ansiedad y depresión, aunque no alcanza la significación en los modelos multivariados.…”
Section: Discussionunclassified
“…El apoyo social es una variable determinante en la adaptación al cáncer (26,27) y por ello se hace necesario controlar su efecto. Dicha variable se ha evaluado mediante el cuestionario MOS de apoyo social (28) (MOS Social Support Survey; MOS-SSS).…”
Section: (Hads)unclassified